2019
DOI: 10.1002/jia2.25276
|View full text |Cite
|
Sign up to set email alerts
|

Distance to clinic is a barrier to PrEP uptake and visit attendance in a community in rural Uganda

Abstract: Introduction Geographic and transportation barriers are associated with poorer HIV ‐related health outcomes in sub‐Saharan Africa, but data on the impact of these barriers on prevention interventions are limited. We estimated the association between distance to clinic and other transportation‐related barriers on pre‐exposure prophylaxis (Pr EP ) uptake and initial clinic visit attendance in a rural community in southwestern Uganda enrolled in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 22 publications
2
36
0
Order By: Relevance
“…Participants residing further away from the KEMRI clinic were more likely to be LTFU. Distance and time taken to travel to the clinic likely contributed to missed study visits and LTFU [26]. Of note, 42% of participants who became LTFU reported that they had relocated outside the study area.…”
Section: Resultsmentioning
confidence: 99%
“…Participants residing further away from the KEMRI clinic were more likely to be LTFU. Distance and time taken to travel to the clinic likely contributed to missed study visits and LTFU [26]. Of note, 42% of participants who became LTFU reported that they had relocated outside the study area.…”
Section: Resultsmentioning
confidence: 99%
“…For example, before COVID-19, HIV testing uptake was already lower in rural and impoverished regions of the country, and among men [9]. Distance to biomedical clinics has also been shown to decrease HIV service utilization in rural Uganda [10,11]. Like much of sub-Saharan Africa, our study region is medically pluralistic, where people seek care from both formal and informal healthcare resources.…”
Section: Implications For Hiv Testing and Epidemic Controlmentioning
confidence: 99%
“…Geographic barriers to care, including physical distance to a health facility, may contribute to poor treatment outcomes. Distance from home to health facility has been associated with decreased access to a wide range of health services and outcomes, including poor HIV treatment clinic attendance [5] and antiretroviral adherence [6], lower likelihood of facility-based childbirth [7], and maternal [8] and child mortality [9]. Geographic barriers to care have been linked to delays [6,10], loss-to follow up [11], and lack of adherence during the TB diagnostic evaluation and treatment processes [10].…”
Section: Introductionmentioning
confidence: 99%